Economic evaluation and cost of interventions for cerebral palsy: a systematic review. (10th January 2018) - Shih, Sophy T F; Tonmukayakul, Utsana; Imms, Christine; Reddihough, Dinah; Graham, H Kerr; Cox, Liz; Carter, Rob
Abstract : Aim: Economic appraisal can help guide policy‐making for purchasing decisions, and treatment and management algorithms for health interventions. We conducted a systematic review of economic studies in cerebral palsy (CP) to inform future research. Method: Economic studies published since 1970 were identified from seven databases. Two reviewers independently screened abstracts and extracted data following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Any discrepancies were resolved by discussion. Results: Of 980 identified references, 115 were included for full‐text assessment. Thirteen articles met standard criteria for a full economic evaluation, two as partial economic evaluations, and 18 as cost studies. Six were full economic evaluations alongside clinical studies or randomized controlled trials, whereas seven involved modelling simulations. The economic case for administration of magnesium sulfate for imminent preterm birth is compelling, achieving both health gain and cost savings. Current literature suggests intrathecal baclofen therapy and botulinum toxin injection are cost‐effective, but stronger evidence for long‐term effects is needed. Lifestyle and web‐based interventions are inexpensive, but broader measurement of outcomes is required. Interpretation: Prevention of CP would avoid significant economic burden. Some treatments and interventions have been shown to be cost‐effective, although stronger evidence of clinical effectiveness is needed. What this paper adds Cost‐effectiveness evidence shows prevention is the most significant strategy. Some treatments are cost‐effective, but stronger evidence for long‐term effectiveness is required. Comparison of treatment costs is challenging owing to variations in methodologies and varying clinical indications. What this paper adds: Cost‐effectiveness evidence shows prevention is the most significant strategy. Some treatments are cost‐effective, but stronger evidence for long‐term effectiveness is required. Comparison of treatment costs is challenging owing to variations in methodologies and varying clinical indications. This systematic review is commented on by Marceniuk on page532 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=poG_Z6ArWEQ&feature=youtu.be